Root Extract of Lindera aggregata (Sims) Kosterm. Modulates the Th17/Treg Balance to Attenuate DSS-Induced Colitis in Mice by IL-6/STAT3 Signaling Pathway - Lai, Huimin; Yang, Zhengbiao; Lou, Zhaohuan; Li, Feng; Xie, Feng; Pan, Wei; Xu, Cong; Zhang, Lili; Zhang, Sheng; Zhang, Lijiang; Huang, Mincong (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic, idiopathic and relapsing inflammatory disease of the gastrointestinal tract that has a prolonged disease duration. Lindera aggregata(Sims) Kosterm. is a traditional Chinese herb which has been used to treat gastrointestinal diseases for thousand years. However, there are few reports about the application of L. aggregata in the treatment of UC at present. Herein, we investigated the therapeutic effect of the root extract of L. aggregata (LREE) against UC and explored its underlying mechanisms based on IL-6 signaling pathway and the balance of T helper (Th) 17 and regulatory T (Treg) cells. Results showed that LREE could not only decrease the production and secretion of IL-6, but also could inhibit the signal transduction of IL-6/STAT3 signaling pathway. Moreover, LREE could significantly inhibit the differentiation of CD4+ T cells to Th17 cells in vitro and decrease the proportion of Th17 cells in mesenteric lymph nodes (MLNs) of model mice in vivo. Besides, LREE could also alleviate the disease symptoms, reduce intestinal permeability and improve histopathological changes of colitis model mice. Together, LREE can significantly inhibit the production and secretion of IL-6, regulate IL-6/STAT3 signal transduction, and modulate the balance of Th17 and Treg cells and effectively attenuate UC.